#Respect: Applying Anderson's Code of the Street to the Online Context. Issue 7 (3rd July 2017) - Henson, Billy; Swartz, Kristin; Reyns, Bradford W.
ABSTRACT: Anderson's work on street codes has become a seminal piece in cultural criminology. Today, it is frequently argued that street-oriented cultural beliefs are strongly linked to criminal offending. While numerous studies have found support for this link, research has yet to examine this relationship as it applies to Internet-based criminal behaviors. The current study attempts to fill this gap by examining both the predictors and effect of similar cultural beliefs in the online context. Results indicate that while controlling for more commonly examined predictors of crime, individuals who adhere to street-oriented beliefs in an online context are more likely to commit cybercrime.